Evaluación del plan estratégico y su ejecución presupuestaria en el cuerpo de bomberos del cantón caluma 2020 – 2021 - Vega Rivadeneira, Alinzon Adrián (2022)
The Caluma Canton Fire Department (CBC) is a non-profit institution located in the city of Caluma, province of Bolívar, created on September 4, 1980, in order to provide citizens with care and protection services against various accidents or natural phenomena. The institution consists of 2 areas; operational and administrative in addition to some departments designated to human talent, personal property and financial management. The fire department of the Caluma canton has a respective strategic plan in which it has proposed its strategic objectives aimed at the administrative area, the risk operational area and the infrastructure; Compliance with this strategic plan is intended to provide greater security to the community in the event of a natural hazard or accident that firefighters have to face to save people, however, there have been problems with it. This report deals with the "Evaluation of the Strategic Plan and its Budget Execution in the Caluma Canton Fire Department 2020 - 2021", this evaluation is carried out with the objective of verifying if the strategic plan has been fulfilled in the institution. This case study is found under the research sublines Audit and Control, and Management of Financial, Tax and Social Commitment Information; The deductive research method was applied and primary techniques such as the use of a questionnaire in the interview with the person in charge of the institution, in addition to having documentary information provided by it, and through this the viability and reliability can be guaranteed. of the information that will reside in this report.